DIGITALIZATION IN LITERATURE LEARNING IN ELEMENTARY SCHOOLS - Yulhasni; Emilda Sulasmi; Faisal Rahman Dongoran (Academic Solution Publisher, 2026)
The way elementary school students access, understand, and create literary texts is transformed by digitalization. However, the use of technology in literature learning often stops at the transfer of printed books to screens without adequate pedagogical design. The purpose of this article is to evaluate the importance of digitization in literature learning in elementary schools, the various types of media that can be used, the advantages and disadvantages of its utilization, and the methods that can be applied to achieve it. This research conducted a literature review using a qualitative descriptive method. The selected coverage comes from books, articles, and reports from international institutions that discuss children's literature, digital stories, multimedia learning, digital literacy, and reading on screens. The data analysis process includes reduction, theme grouping, result comparison, and conclusion drawing. The research results show that when multimedia elements align with learning objectives, such as digital stories, e-books, digital comics, animated videos, story production projects, and engagement, vocabulary, story comprehension, writing skills, and digital literacy, students can be improved. However, irrelevant interactions, screen use without guidance, inappropriate device usage, excessive animations, and the lack of digital skills among teachers can reduce student comprehension and increase the learning gap. Therefore, digitalization should be seen as an enhancement and not a replacement for reading, discussion, appreciation, and value reflection activities. Content quality, teacher readiness, equitable access, child data protection, and literacy-focused learning evaluation are all factors that determine the success of implementation.